KUALITAS INFORMASI TERHADAP CITRA DESTINASIPASAR TERAPUNG PADA WISATAWAN DOMESTIK - Najla Amaly (UIN Antasari Banjarmasin, 2017)
This study aimed to identify the effect on the image quality destination information Travel Floating Market on domestic tourists who are domiciled in the city of Banjarmasin. In the year 2014-2015 has been designated as the year for the promotion of South Kalimantan province in the restructuring program of Library Air Travel Banjarmasin by the local government. This program has continued to the present, so that the local government is still heavily in the promotion tours. The local government has made tourism promotion through marketing communications mix. Particularly Travel Floating Market is an icon of South Kalimantan which became the main attraction which was appointed by the local government to promote the city of Banjarmasin as the City of a Thousand Rivers. But over the years there has been no attempt to evaluate the results of the promotion. Whether the information provided has been perceived positively by tourists or not. BPS data from Banjarmasin has occurred rise and fall of the number of tourist visiting the city of Banjarmasin. In 2014 the decline in the number of tourists visiting the city of Banjarmasin. Banjarmasin city government that has never evaluates whether the information of the marketing communications mix Banjarmasin Floating Market has succeeded in creating a positive image for tourists. This study uses the theory of S-O-R where stimulus effect on the response. This research is a quantitative explanation. By distributing questionnaires to 100 respondents of research, the results of this study based on the analysis done by simple linear regression analysis, it can be concluded that the quality of information significant effect on the image of the destination. Values influence of independent variables in this study has a value of 27.4% in affecting the image of the destination.